Practice of COVID-19 Preventive Measures and its Associated Factors among the Undergraduate Medical Students: A Cross-Sectional Study - Mishra, Anjali; Bhattarai, Karuna; Karki, Sulata; KC, Heera; Parajuli, Surya Bahadur (Birat Journal of Health Sciences, 2022)
Introduction: The COVID-19 is an emerging infectious disease with serious public health consequences. Appropriate practice of preventive measures and adherence to it play an essential role in reducing infection rates and controlling the spread of the disease. Objectives: This study aimed to assess the practices of COVID-19 preventive measures and its associated factors among the undergraduate medical students at Birat Medical College Teaching Hospital. Methodology: A cross-sectional study was conducted from 25 July 2021 to 25 December 2021 among the medical students at Birat Medical College Teaching Hospital, Morang, Nepal. The complete enumeration of 146 medical students were carried out. Ethical clearance was obtained from the Institutional Review Committee at Birat Medical College Teaching Hospital. A semi-structured questionnaire using Google forms was used for data collection. Univariate and bivariate analysis were done. A p-value less than 0.05 was considered statistically significant. Results: The mean score for practices of preventive measures towards COVID-19 was 16.58±2.73. More than half of the participants (54.1%) adopted good practices. The most frequently performed practice was wearing face masks when going outside the home (98.6%), followed by hand washing using soap and water for at least 20 seconds regularly (96.6%) and covering the mouth when coughing or sneezing with a tissue paper/a disposable handkerchief (96.6%). Moreover, most of the participants used alcohol-based hand sanitizer if soap and water were not available (95.2%), stayed at home when they felt flu-like symptoms (95.2%), visited the nearest health facility when getting sick (95.2%), and avoided close contact with sick individuals with flu-like symptoms (93.2%). Age, gender, ethnicity, religion, marital status, academic year, average monthly family income, any health insurance and vaccination status were not significantly associated with the practice of COVID-19 preventive measures. Conclusion: More than half of the participants adopted good practices of preventive measures towards COVID-19. Lower practice scores among medical students is the matter of concern.